Novel Hydrogel Membranes Based on the Bacterial Polysaccharide FucoPol: Design, Characterization and Biological Properties - Araújo, Diana (2023)
FucoPol, a fucose-rich polyanionic polysaccharide, was used for the first time for the preparation of hydrogel membranes (HMs) using Fe3+ as a crosslinking agent. This study evaluated the impact of Fe3+ and FucoPol concentrations on the HMs’ strength. The results show that, above 1.5 g/L, Fe3+ concentration had a limited influence on the HMs’ strength, and varying the FucoPol concentration had a more significant effect. Three different FucoPol concentrations (1.0, 1.75 and 2.5 wt.%) were combined with Fe3+ (1.5 g/L), resulting in HMs with a water content above 97 wt.% and an Fe3+ content up to 0.16 wt.%. HMs with lower FucoPol content exhibited a denser porous microstructure as the polymer concentration increased. Moreover, the low polymer content HM presented the highest swelling ratio (22.3 1.8 g/g) and a lower hardness value (32.4 5.8 kPa). However, improved mechanical properties (221.9 10.2 kPa) along with a decrease in the swelling ratio (11.9 1.6 g/g) were obtained for HMs with a higher polymer content. Furthermore, all HMs were non-cytotoxic and revealed anti-inflammatory activity. The incorporation of FucoPol as a structuring agent and bioactive ingredient in the development of HMs opens up new possibilities for its use in tissue engineering, drug delivery and wound care management.